I do not remember how to do the operations to solve these types of equations... x/-7 + 9 = 6 and the problem x/-4 + (-7) = (-16). what is the difference and how do you work them out?
First thing you do is take get everything on the opposite side of x. To do that, start by taking the parenthesis off first. Then take the (-7) and moving it over.
x/-4 + (-7) = (-16)
x/-4 - 7 = -16
x/-4 - 7 + 7 = -16 +7 Remember, whatever you do to one side, you have to do to the other.
x/-4 = -9 Now multiply both sides by -4
x= 36 Remember, the negatives cancel out
Now plug it back into the the original equation to see if it works.